Efeito da modificação térmica em escala industrial na qualidade da madeira de Tectona grandis Linn. F. - Menezes, Walmir Marques de (2017)
The process of the thermal modification on wood is the application of heat in order to improve its quality. The objective of this research was to evaluate the effect of the thermal modification in industrial scale on the wood quality of Tectona grandis Linn. F. To this end, boards of approximately 35 x 100 x 2200 mm (thickness, width and length), separated and numbered in quality classes. First-class boards were with the highest presence of core and free of defects, such as cracks, knots, warps, among others, while the second class boards presented larger portions of sapwood and defects mentioned above. In this way, four batches of wood were separated into four treatments, with T1 and T2 being the natural wood of the first and second quality respectively, and in the same order of quality, however, the T3 and T4 treatments were thermally modified. The original pieces of 2200 mm length were divided into two pieces of equal size (1100 mm), one of them corresponding to the wood control (T1 and T2), that is, the non-thermally modified, for later comparison with the treated wood (T3 and T4). The VAP HolzSysteme® thermal modification was conducted according to the program used by the company, where the final temperature was 160 ° C. After the heat treatment, the wood was tested by the quantification of defects; Effect on chemical composition; In the physical and mechanical properties, and, finally, of the resistance to xylophagous fungi. The defects were analyzed by the standard NBR 9487 (ABNT, 1986) through cracks (top and surface) and warping (bending, bending and recessing). In addition, the moisture content was also measured. The chemical analyzes followed the methodologies described in the Technical Association of Pulp and Paper Industry - TAPPI (Tappi, 1999), through the analysis of total extractives, lignin Klason, holocellulose, hemicellulose and alpha cellulose. For the physical tests (equilibrium moisture content, apparent specific mass, total swelling and swelling anisotropy), the procedures established in ASTM D 143-94 (ASTM, 2000) were used. Colorimetry followed ASTM D 2244-09a (ASTM, 2009). The test of static flexion and parallel compression of the fibers followed the standard ASTM D 143-94 (ASTM, 2000). The test of shear strength in parallel compression to the fibers in the glue line was according to ASTM D - 905 (ASTM, 2008a) and the percentage of failure of the specimens, followed the standard ASTM D - 3110 (ASTM, 2008 b). The assembly of the biological analyzes followed the recommendation of the European norm EN 113 (1996). The fungus used was Ganoderma applanatum (white rot) and the resistance was evaluated by the ASTM D 2017 standard. The heat treatment influenced the increase of the moisture content, but this did not interfere with the quality of the wood. The quality of the thermal modification was satisfactory, if evaluated by the defects of cracks and warpage. In addition, the quality of the wood was paramount for the lowest defect rate. The content of extractive and alpha cellulose increased significantly with thermal modification, in contrast, holocellulose and hemicellulose reduced, and still, for the latter, the quality of the wood may have influenced. The Klason lignin content was not significantly altered by temperature or by the quality of the wood. The equilibrium moisture content, apparent specific mass of the wood, total swelling and anisotropy of wood swelling decreased after heat treatment, due to loss of hemicellulose mass and increase of total extractives. Therefore, the dimensional stability of the wood has been increased. The colorimetry was influenced by the thermal modification of the wood, through the darkening and increase of the reddish hue. The quality of the wood did not influence the physical properties, except the colorimetry, which was altered by the difference in the proportion of the sapwood and core of the specimens. The failures in the wood caused by the shear strength in the glue line were satisfactory. The mechanical strength of all tests was reduced by the quality of the wood and the thermal modification, which in the latter case caused hemicellulose degradation. The wood was considered very resistant, although the loss of mass in contact with the fungus increased in the thermally treated wood. The results may have been influenced by the quality of the wood and the degradation of the hemicelluose. It was concluded that, in general, the effect of the thermal modification on the quality of the wood was significant in all evaluated properties (chemical, physical, mechanical and biological), and the presence of heartwood, sapwood had little influence. The main responsible for the changes in the wood after the thermal modification was the degradation of hemicellulose.